Wymierzanie odpowiedzialności karnej za niedostosowanie się do zakazów i nakazów pandemicznych po ich uchyleniu (o rozbieżności w uznawaniu depenalizacji nienoszenia maseczek w miejscu nakazanym wobec znoszenia rozporządzeń covidowych) - Karakulski, Jacek (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The aim of this article is to analyze the situation in which the enforcement of criminal (misdemeanor) liability for the violation of temporary pandemic restrictions must be pursued after the repeal of episodic Covid regulations. The presented text addresses issues related to (i) the scope of application of the lex mitior agit principle, (ii) the decriminalization, (iii) the impact of the reasons for the repeal of certain provisions on the applicability of prohibitions and orders derived from those provisions and the assessment of the unlawfulness (ex tunc) of an offense, and (iv) the various ways in which the legislator formulated the temporal scope of the episodic Covid regulations. One of the conclusions of the research is that the principle expressed in Article 2 § 1 of the Polish Code of Petty Offences does not constitute an obvious obstacle to prosecuting the perpetrator of a Covid offense after the regulation constituting the basis for the legal standards of the prohibition and injunction has been repealed. In the case of lifting the obligation to cover the mouth and nose (which is a particularly frequent subject of proceedings before the court in the scope of Article 116 § 1a of the Polish Code of Petty Offences), there are no reasons to infer that punishment cannot be imposed from the fact of derogation of the provisions that grounded the assessment of the unlawfulness of the action. The issue of the enforcement of already imposed penalties was deliberately omitted in the considerations, as the discussed problems have many aspects. The analysis was focused on the current adjudication of criminal liability.